Satisfaction and perceived usefulness with newly-implemented Electronic Health Records System among pediatricians at a university hospital. (February 2019) - Alsohime, Fahad; Temsah, Mohamad-Hani; Al-Eyadhy, Ayman; Bashiri, Fahad A.; Househ, Mowafa; Jamal, Amr; Hasan, Gamal; Alhaboob, Ali A.; Alabdulhafid, Majed; Amer, Yasser S.
Highlights: Higher levels of satisfaction with newly implemented EHR in the developing countries were associated with its perceived positive effect on individual performance and patient care. Better IT support with new EHR implementation and hardware availability may improve satisfaction. Time needed for patient's data entry warrants attention to improve satisfaction. Prompt super-users and IT support in response to feedback from healthcare workers during the launch of a new EHR system may improve system use. Abstract: Background: Apposite implementation of Electronic Health Records (EHR) is anchoring standards of care in healthcare settings by reducing long-run operational costs, improving healthcare quality, and enhancing patient safety. Objective: This study aims to explore factors that might influence Pediatricians' satisfaction with an implemented EHR system and its perceived usefulness at a tertiary-care teaching hospital, Riyadh, Saudi Arabia. Methods: A cross-sectional survey distributed to all physicians working in the pediatric department of King Saud University Medical City (KSUMC) in the period from June to November 2015, two months after the launch of the EHR system, internally branded as electronic system for integrated health information (eSiHi). Bivariate and multivariate regression were analyzed to examine factors associated with physicians' satisfaction. Results: Of the 112 physicians who completed the survey, 97 (86.6%) attended training courses before the implementation of new EHR. On average, the participants rated the perceived usefulness of the new system at 6.4/10 for patient care and physicians' satisfaction levels were 5.2/10. The top indicator of EHR usefulness was the system's ability to reduce errors and improve the quality of care [mean 3.31, SD 0.9, RII 82.8%]; the lowest-ranking indicator was the physicians' perceived familiarity with functions and benefits [mean 2.68, SD 0.7, RII 67%]. The top indicator of satisfaction with the EHR system was enhanced "individual performance" [mean 3.04, SD 1, RII 60.9%]; the lowest-ranking perceived indicator was the limited availability of workplace computers [mean 1.91, SD 1.2, RII 38.2%]. Conclusions: Limited data regarding EHR implementation and end-users satisfaction in the Middle East region necessitates further work on factors affecting levels of satisfaction with the EHR system among different health institutes. Lack of information technology (IT) support, hardware, and time-consuming data entry process are challenging barriers for proper utilization of EHR for pediatric health care services.